A within-person examination of the effect of mentors’ daily ostracism on protégés’ displaced aggression and in-role performance - Li, Miaomiao; Wu, Lunwen; Qin, Yinglin (Frontiers in Psychology, 2023)
Mentors’ ostracism—mentors’ failure to support their protégés when it is socially appropriate to do so—has negative consequences for protégés’ emotions and behaviors. Although research on ostracism has recently flourished, there have been few theoretical and empirical examinations of dynamic, within-person processes related to mentors’ ostracism. Drawing on social information processing theory and social comparison theory, we test how mentors’ daily ostracism triggers protégés’ envy, thus leading to decreased in-role performance and increased displaced aggression. Using an experience sampling study across three work weeks, we found that mentors’ daily ostracism increased protégés’ envy, which resulted in decreased in-role performance and increased displaced aggression. Moreover, our results suggested that mentorship quality might have a dampening moderating effect on the relationship between mentors’ ostracism and protégés’ emotions (i.e., envy). We discuss the theoretical implications of our findings for research on mentors’ ostracism, protégés’ emotions, and protégés’ behaviors.